Velocity Field Analysis of a Channel Narrowed by Spur-dikes to Maximize Power Output of In-stream Turbines - Canilho, Hugo Daniel Leitão (2020)
Decentralized energy is growing in importance with time. The electricity being needed even in the most remote places, far from power stations, increases the importance of small power production devices such as micro-hydro devices like turbines. In this research, the velocity field in a meandering channel is studied in its natural conditions and with the introduction of spur-dikes, structures that prevent bank erosion, a natural phenomenon observed in meandering channels, with the use of computational fluid dynamics software. With the objective of improving the power production by investigating the changes of the flume velocities with the introduction of spur-dikes, one test without any spur-dike and three tests with it were conducted. Good results were reached, with velocities increasing between 10 to 20% with the introduction of these structures. In certain cases, the increase in power production can reach up to 85% than in a normal situation without spur-dikes in the river.